Evaluation of the mini T-plate for fixation of distal radial fractures in puppies and small breed dogs - Rajavardan, K.; Chandrasekhar, E.L.; Raghavender, K.B.P.; Purushotham, G. (Indian Journal of Veterinary Surgery, 2026)
The present clinical study was conducted on six young dogs presented with distal radial fractures. The fractures were treated by internal fixation using 2.0 mm or 2.7 mm mini T-plates. Fractures stabilized with 2.0 mm or 2.7 mm mini T-plates produced rigid fixation in all the six dogs. Immediate postoperative radiographic examination showed good apposition and alignment of the fracture fragments in all the six dogs. Follow-up radiographs revealed primary bone healing with minimal callus formation. The serum alkaline phosphatase and calcium values increased significantly from day 0 to day 14, and thereafter returned to normal values by 45th postoperative day. From the present study it was concluded that the mini T-plates provided satisfactory stabilization of distal radial fractures in small dogs particularly when the distal fragment was small.